2015
DOI: 10.3906/kim-1404-76
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of NADPH-cytochrome P450 reductase from Lake Van fish liver microsomes and investigation of some chemical and metals' effects on the enzyme activity

Abstract: NADPH-cytochrome P450 reductase was purified from Lake Van fish liver microsomes by primary and secondary DEAE-cellulose column chromatograph with 20.46 µ M/min/mg enzyme specific activities, 54.4% purification yield, and purification of 38-fold. The purity of the enzyme was established, and its monomer molecular weight was determined by SDS-polyacrylamide gel electrophoresis. SDS-PAGE results showed a single band and the molecular weight of NADPH-cytochrome P450 reductase was 70 kDa. In addition, optimum ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…The enzymatic activity of NADPH-dependent cytochrome P450 reductase remained almost unaltered in a broad pH range (from 5 to 10 the relative activity was >70%), with a maximum value at pH 8 ( Figure 3 A). These results are similar to results published using other marine fish CPRs, such as Ls CPR (90% relative activity in the pH range 7–8) [ 27 ] or At CPR (82% relative activity in the pH range 7–8) [ 32 ], or the CPR from green microalga Botryococcus braunii (>90% relative activity in the pH range 7–8) [ 34 ]. In addition, Lk CPR also displayed around 40% of relative activity at pH 2 and pH 12, values much higher than those reported for other CPR enzymes at these pH values.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The enzymatic activity of NADPH-dependent cytochrome P450 reductase remained almost unaltered in a broad pH range (from 5 to 10 the relative activity was >70%), with a maximum value at pH 8 ( Figure 3 A). These results are similar to results published using other marine fish CPRs, such as Ls CPR (90% relative activity in the pH range 7–8) [ 27 ] or At CPR (82% relative activity in the pH range 7–8) [ 32 ], or the CPR from green microalga Botryococcus braunii (>90% relative activity in the pH range 7–8) [ 34 ]. In addition, Lk CPR also displayed around 40% of relative activity at pH 2 and pH 12, values much higher than those reported for other CPR enzymes at these pH values.…”
Section: Resultssupporting
confidence: 88%
“…SDS-PAGE gel of the purified enzyme showed a single band around 75 kDa ( Figure 1 ). This molecular weight is similar to that of CPRs from the fishes Liza saliens ( Ls CPR, Mw 77 kDa [ 27 ]) and Alburnus tarichi (Lake Van fish, At CPR, Mw 70 kDa [ 32 ], but is lower than the one of the CPR monomer from the marine fish Stenotomus chrysops ( Sc CPR) (Mw 82.6 kDa) [ 26 ].…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…20 Moreover, it is observed that lipid peroxidation products and oxidative stress increased by a considerable amount in the brain tissues of rats administered 500 ppm lead. 12 In addition, researchers have frequently reported the effects of heavy metal ions on different enzymes in previous years and inhibition effect of heavy metals on metabolically imported enzyme such as CA 21 , glucose 6-phopsphate dehydrogenase 22 , cytochrome P450 reductase 23 , glutathione S-transferase 24 have been determined. For example, Ekinci et al 17 and co-workers mentions the inhibition effects of lead, copper, cobalt heavy metals on cytosolic human CA I and II enzyme activities.…”
Section: Discussionmentioning
confidence: 99%